Socialization and Training of Article 23 Income Tax in Kerinjing Village, Ogan Ilir District - Budiman, Anton Indra; Ermadiani, Ermadiani; Tjandrakirana, Rina; Soediro, Achmad; Kusumawardani, Media; Adhitama, Fardinant; Yusrianti, Hasni (Faculty of Economics, Universitas Sriwijaya, 2022)
The implementation of laws and regulations regarding villages still has many problems that must be addressed properly and as early as possible. Problems start from the aspect of human resources, regional and village regulations that have not been compiled, the readiness of village documents that are not yet available and so on. Training on Income Tax Article 23 is expected to be able to provide solutions to aspects of improving human resources. The objects of this community service activity are all village government officials who are responsible for managing village finances. The training given to training participants uses the pedagogical learning method, where the speaker provides training with a monologue then continues with a two-way dialogue between the resource person and the participant. Community service activities are carried out in Kerinjing Village and carried out within 2 days. The results of this training can be concluded that: 1) The role of village officials in Kerinjing Village, Tanjung Raja Ogan Ilir sub-district in relation to Income Tax Article 23 is very large; 2) There is a suitability of training material with the needs of village officials to increase understanding of Article 23 Income Tax; 3) There is a positive response seen from the enthusiasm of the training participants to participate in service activities; 4) There needs to be assistance for village officials in calculating, calculating, paying, reporting in relation to Income Tax Article 23. Especially in relation to tax notification (SPT) both periodic and annual SPT.